2014
DOI: 10.1002/asi.23050
|View full text |Cite
|
Sign up to set email alerts
|

Where your photo is taken: Geolocation prediction for social images

Abstract: Social image-sharing websites have attracted a large number of users. These systems allow users to associate geolocation information with their images, which is essential for many interesting applications. However, only a small fraction of social images have geolocation information. Thus, an automated tool for suggesting geolocation is essential to help users geotag their images. In this article, we use a large data set consisting of 221 million Flickr images uploaded by 2.2 million users. For the first time, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Other proposals are focused on discovering popular tourist attractions within the urban areas through geo-tagged images posted in Flickr [47] or Panoramio [48]. These platforms are SNSs where users can share, organize, and find multimedia content composed mainly of pictures [49,50].…”
Section: Analysis Of Social Network Sites For Informational Urbanismmentioning
confidence: 99%
“…Other proposals are focused on discovering popular tourist attractions within the urban areas through geo-tagged images posted in Flickr [47] or Panoramio [48]. These platforms are SNSs where users can share, organize, and find multimedia content composed mainly of pictures [49,50].…”
Section: Analysis Of Social Network Sites For Informational Urbanismmentioning
confidence: 99%
“…This is what makes geotagged images and status updates valuable to commercial companies for advertising, user profiling, and other uses such as studying consumption patterns on a particular street. Because "a large portion of photos uploaded to social image-sharing services contain no geolocation information" (Liu et al, 2014), companies have created automated systems that detect the location shown in the photograph to prompt users to geotag both new and older content. A study of images posted to Flickr found that less than 50% were geotagged (Liu et al, 2014).…”
Section: Geotagging and Market Valuementioning
confidence: 99%
“…Because "a large portion of photos uploaded to social image-sharing services contain no geolocation information" (Liu et al, 2014), companies have created automated systems that detect the location shown in the photograph to prompt users to geotag both new and older content. A study of images posted to Flickr found that less than 50% were geotagged (Liu et al, 2014). Interestingly, this study used the time lapse between capturing the image and geotagging it as one of the methods of analyzing user geotagging behavior (Liu et al, 2014).…”
Section: Geotagging and Market Valuementioning
confidence: 99%
See 1 more Smart Citation
“…Kennedy and Naaman [39] used visual features and tags, in order to extract the most representative tags and views for landmarks, working on a corpus of 110K Flickr photos from San Fransisco. Finally, Liu et al [40] were the first to consider user uploading patterns, geotagging behaviors, and the relationship between the temporal and the spatial gap of two photos from the same user.…”
Section: A Little Bit Of Both -The Hybrid Approach!mentioning
confidence: 99%